The accommodation of cognitive style in the design of human computer interface - Parkinson, Adrian Brendan Kenneth (Trinity College (Dublin, Ireland). School of Computer Science & Statistics, 2006)
How the design of the human computer interface could be varied to accommodate specific cognitive styles is addressed. The area of adaptive versus non-adaptive systems was discussed in Chapter 2. Generally non-adaptive systems were favoured due to the difficulties pertaining to adaptable and adaptive systems. Chapter 3 reviews the Cognive Styles' literature. Generally there have been concerns about the reliability and validity of cognitive styles. The definition and measurement of cognitive styles is still problem atic. The accommodation of cognitive style in interface design is discussed in Chapter 4. This discussion involves i. a review of the literature, ii. two empirical studies examining the accommodation of individual differences (cognitive styles) in the human computer interface (HCI), and iii. a consideration of the matching/mismatching hypothesis which underlies their accommodation. These two studies are evolutionary and lead on to the direct accommodation of cognitive style in the HCI by means of a test.
Keywords: Computer Science, Ph.D.; Ph.D. Trinity College Dublin